Islamic parenting education in the success of the 'Aisyiyah of love children movement - Nurul Kurniati; Enny Fitriahadi; Islamiyatur Rokhmah; Hari Akbar Sugiantoro (Universitas Muhammadiyah Magelang, 2023)
Special attention to children as individuals who are still in their developmental age is certainly no less important, because childhood is a process towards maturity. Use of gadgets that are not ideal for more than 2 hours per day can result in attention deficit disorder in children which causes anxiety, anger, and so on. If left untreated, it can have an impact on the child's psychology and disrupt the child's development. One of Aisyiyah's roles as a women's organization was declaring the 'Aisyiyah of love children movement. The purpose of this program is to improve the quality of children with Islamic parenting educational activities. The method used is counseling and outreach. The result is an increase in understanding from teachers in the good category from 67% to 93%, and parents' understanding in the good category from 71% to 96%. After this program, it is hoped that health monitoring can be carried out on an ongoing basis, one of which is screening for growth and development of toddlers.